Efficacy of salicylic acid incorporated with lukewarm water immersion on postharvest quality of ‘Leb Mue Nang’ bananas (Musa AA) on shelf life storage - Youryon, Pannipa; Nokkhao, Ruamjit; Suemak, Aphisit; Supapvanich, Suriyan (Agriculture and Natural Resources, 2025)
Importance of the work: The shelf life of ‘Leb Mue Nang’ bananas (Musa AA) is relatively short. The decline in quality with shelf life limits the market presence of bananas. Objectives: To investigate the impact of salicylic acid (SA) incorporated with lukewarm water (LW) immersion on the quality preservation of ‘Leb Mue Nang’ bananas stored under shelf life conditions (27 ± 2°C, 65 ± 8% relative humidity) for 6 d. Materials and Methods: First, the effects on banana quality were monitored of SA immersion at 0−2 mM, as well as LW immersion at 45 or 50°C for 5−15 min. Consequently, the impact was examined of SA+LW (SA at 0.25 mM combined with LW at 45°C for 15 min) on the quality preservation of bananas compared to the SA-only, LW only and control treatments. Results: In the preliminary study, the bananas subjected to 0.25 mM SA dipping or LW at 45°C for 15 min best preserved postharvest quality. Compared to the control, all treatments delayed senescence spots and maintained pulp firmness, as well as postponing increases in weight loss, total soluble solids content, total acidity and ripening index. Both the SA and SA+LW treatments increased the total phenols and antioxidant activity. The SA+LW treatment decreased skin damage and preserved pulp firmness compared to the SA- and LW-only treatments. All examined quality parameters were significantly and positively correlated during storage, with the exception of pulp firmness, which had a negative correlation to the other parameters. Main finding: The SA+LW treatment effectively preserved the quality and prolonged the shelf life of the ’Leb Mue Nang’ bananas compared to untreated fruits.